Conservation of Medicinal and Aromatic Plants for Better Cultivation Mode Leading towards Biodiversity - Khan, Sher Wali; Hussain, Azhar; Ali, Sartaj; Abbas, Aqleem; Roomi, Ishrat (Current Research Progress in Agricultural Sciences Vol. 3, 2024)
Medicinal and aromatic plants (MAPs) provide various ecological, economic, and cultural benefits, including food, medicine, clothing, and shelter. However, uncontrolled and unsustainable collection practices are leading to their rapid depletion and eventual extinction. This indiscriminate collection threatens the status of several high-value MAP species, causing habitat damage and biodiversity loss. Over 80% of the world's population still depends on plant-based traditional medicines, making the conservation of MAPs crucial for the sustainability of life on Earth. To address this issue, the chapter suggests utilizing cutting-edge techniques such as in-situ and ex-situ conservation and cultivating medicinal crops in agricultural areas. Cultivating medicinal crops offers several advantages, including high local and international demand, better returns, and fewer resource requirements. This approach can help conserve and sustainably utilize high-value medicinal and aromatic plants while providing economic benefits to farmers. The book chapter aims to raise awareness among researchers, farmers, and other stakeholders about the potential benefits of adopting new crops and addressing issues during the cultivation of medicinal plants. By conserving and sustainably utilizing high-value medicinal and aromatic plants, we can ensure the well-being of the planet and its inhabitants.